Tindak Tutur Asertif dalam Drama Series Imperfect The Series Season 2 Episode 1 - Fatikhah, Nur; Sudirman, Nurul Aini; Fadillah, Nurul; Alber, Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Assertive speech acts function to say or convey something. In the drama series imperfect the series season 2 episode 1, there are many utterances that contain assertive speech acts. The problem in this study is how assertive speech acts are in the drama series imperfect the series season 2 episode 1. This study aims to describe, analyze and interpret assertive speech acts in the drama series imperfect the series season 2 episode 1. Data collection is from May 8, 2023 until June 7, 2023, which amounts to 14 data. The method used in this study is a qualitative approach in which the results of the data will be in the form of writing not numbers in the form of speech, so that the results of the data are in the form of utterances from conversations that have been observed. The results of the study show that there are assertive speech acts in the drama series imperfect the series season 2 episode 1. The researchers found four assertive speech acts with the functions of informing, suggesting, complaining, and boasting. Assertive speech act informs that there are 7 utterances, assertive speech act suggests finding 6 utterances, assertive speech act complains the researcher finds 4 utterances, then assertive speech act boasts there are 2 utterances.